Penentuan Pola Pembelian Sparepart Pada PT Shavard Andalan Global Dengan Metode Apriori - Andre Raymon Rangian; Saghifa Fitriana (Paradigma, 2022)
In the business world, data is very important information for companies to develop their business space. In the business space of a company, by maximizing the quality of a product. The realm of the business world, especially maintenance such as spare parts, agents, and workshops, is required to be able to promote its business strategy in selling spare parts. The strategy that must be carried out is with good service for consumers such as providing stock of goods so that there is no stock of spare parts that are often purchased by consumers and the goods sold are not defective. Data mining is in the form of knowledge or information by looking for certain patterns or rules from a number of data. In Data Mining there are many methods, one of which is the association method or often called Association rules mining. Therefore, the availability of various types of spare parts and the number of items in Shavard must be recorded every day in order to support and maintain smooth distribution to consumers, so that customer service activities run well. Data mining is able to create an intelligent business environment, to face the increasingly high level of competition in the spare parts business in the future. Data mining produces association rules between items in January 2019 to December 2019, known patterns of spare parts sales. If you buy P&RK, you will buy ACI and DH SV-512 with a support value of 33% and a confidence value of 66.67%.